TUBERCULOSIS OF STOMACH - Javed, Mohammad; Ahmed, Sajjad (Journal of Ayub Medical College Abbottabad, 1995)
Tuberculosis is still a major health problem in Pakistan.1 No organ of the human body is spared. After lungs, the Gastrointestinal tract is the most frequently affected area2. In the GIT however involvement of the stomach is very rare3. We report a case of gastric tuberculosis in a 55- year-old man.